2011
DOI: 10.1111/j.1600-6143.2011.03464.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful ABO-Incompatible Kidney Transplantation with Antibody Removal and Standard Immunosuppression

Abstract: ABO-incompatible (ABOi) kidney transplantation is an established therapy, though its implementation to date has been in part limited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
101
2
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 26 publications
11
101
2
16
Order By: Relevance
“…Flint et al (13) recently reported their prospective, observational experience with 37 ABOincompatible transplant recipients (52 contemporaneous ABO-compatible recipients acted as a comparator group). They found a BK viremia rate of 13% but no cases of BKVAN in the ABO-incompatible group (compared with 19% and one case of BKVAN in the ABO-compatible group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flint et al (13) recently reported their prospective, observational experience with 37 ABOincompatible transplant recipients (52 contemporaneous ABO-compatible recipients acted as a comparator group). They found a BK viremia rate of 13% but no cases of BKVAN in the ABO-incompatible group (compared with 19% and one case of BKVAN in the ABO-compatible group).…”
Section: Discussionmentioning
confidence: 99%
“…Risks and benefits of performing transplantation across the blood-group barrier are well documented (6-9), but a link between ABO-incompatible kidney transplantation and risk for BKVAN is contentious. Some groups have observed a higher risk for BK viremia or nephropathy (10)(11)(12), whereas others have not (8,13). The implication is that ABO-incompatible kidney recipients may be at greater risk for development of BK viremia or nephropathy because of increased intensity of induction protocols and subsequent immunosuppressant burden (both maintenance and treatment of cellularand antibody-mediated rejections).…”
Section: Introductionmentioning
confidence: 99%
“…Los centros evalúan diversas técnicas de determinación de isoagluti ninas, dado que su exacta medición es determinante para el monitoreo de la desensibilización (32) . Los tí tulos iníciales de anti cuerpos naturales anti -A2 (Ig G 1/128, Ig M 1/128) presentes en el paciente, requerían un número mayor de sesiones de recambio plasmáti co para alcanzar niveles de seguridad aceptables previo al trasplante (menor de 1/8) (33) . La mayoría de centros identi fi ca un nivel de tí tulo de corte para exclusión de candidatos potenciales (9) y eligen por ejemplo como 1/8 el límite superior aceptable para el día del trasplante.…”
Section: Discussionunclassified
“…La individualización de los protocolos de desensibilización minimizando el núme-ro de sesiones de recambios plasmáti cos es la tendencia recomendable (9) . Actualmente, evitar la esplenectomía es relevante en los protocolos, por las complicaciones que conlleva, y solo se reserva para un pequeño número de pacientes como terapia de rescate en rechazos mediados por anti cuerpos de intensidad severa (5,33) . La plasmaféresis más que la inmunoadsorción es recomendada sobre todo para pacientes sensibilizados a fi n de remover los anti cuerpos anti -HLA y los anti cuerpos anti -ABO, como en nuestro caso (13,26,32,37) .…”
Section: Discussionunclassified
“…Bu nedenle transplant sonrası dönemde primer hastalık nüksü veya rejeksiyon gelişim riski yüksek olan gruplar özellikle belirlenmeli ve gerekli önlemler (6). ABO uyumsuzluğunda genel yaklaşım transplant öncesi 2-4 seans plazmaferez, sonrasında splenektomi veya rituksimab+İVİG uygulanmasıdır (7)(8)(9). İmmünadsorbsiyon işlemi spesifik olarak Anti-A ve Anti-B antikorlarını uzaklaştırdığı için PE tedavisine göre daha yararlıdır (10).…”
Section: Introductionunclassified